Introduction to the assessment of the quality of non-financial reports of banks in the context of WIG-ESG index membership - Chamera Klaudia Olga (Journal of Economics and Management)
Aim/purpose – This article aims to conduct a preliminary assessment of the quality of non-financial reports of banks considering their membership in the WIG-ESG index on the Warsaw Stock Exchange (WSE). The research problem addresses whether the quality of reports from WIG-ESG banks is higher than that of those outside the index.